Integration of Multicultural Principles in Elementary Madrasahs: A Systematic literature review - Masykur, Ali; Ilmiah, Rikhlatul (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2023)
The discussion related to the application of multicultural values through Madrasah Ibtidaiyyah educational institutions aims to describe what valuescan be applied and how. The research method used is the library research method using descriptive analysis techniques. Democracy, tolerance and harmony are some of the values summarized in the concept of multicultural values. These three are essential values for society to understand in the process of becoming a nation and state. All three will be able to be understood and actualized when implemented well. One of the factors for implementing multicultural values is through an educational process that has a multicultural perspective. The educational process to apply these values should be carried out through all lines of education, both regular educational institutions and community educational institutions. One institution that deserves attention is the Ibtidaiyyah madrasah. This institution is a flexible institution and is also an institution that is in the community environment. In this way, this institution develops into an institution that is ready to transform multicultural values. Some things that must be done are (a) reorganizing the curriculum and learning; (b) preparing superior teaching staff, (c) creating an agenda for cross-religious and cultural harmony, and (d) making the public aware of the importance of madrasah ibtidaiyah.